TAKE THE RISK OR LOSE THE CHANCE! CASE REPORT - G. Tsvetkova; Y. Zdravkov; A. Oscar (Trakia Journal of Sciences)
The hallmark of keratoconus is central or paracentral stromal thinning, accompanied by apical protrusion and irregular astigmatism. Patients typically experience variable reductions in visual acuity, image distortion, and increased sensitivity to glare and light. The latter becomes of major interest when patients with keratoconus present with a cataract which contributes to a further visual decline. PURPOSE: To present a case report of a patient who underwent cataract surgery, with implantation of an intraocular implant called pinhole and correction of an irregular corneal astigmatism as a result of keratoconus. METHODS: A report of a rare case, the first implantation of XtraFocus implant in Bulgaria for the correction of keratoconus combined with cataract. RESULTS: All necessary measurements were performed using an iTrace aberrometer and IOL Master 700. The cataract removal was performed by standard phacoemulsification followed by implantation of a pinhole implant in the capsular bag. No complications related to the position of the implant were observed in the postoperative period. Optimal correction of the distance vision and near vision was achieved, and the results were monitored within six months after surgery. CONCLUSION: The pinhole implant was securely positioned in the capsular bag. Well tolerated by the patient, the implant played a key role in effectively overcoming the irregular corneal astigmatism. There is a significant improvement in visual acuity with results satisfying the patient's high expectations.